Unraveling the Performance of Islamic Banking: An Analysis of Determinant Factors of Islamic Commercial Banks’ Financing 2018 ̶ 2023 - Wijayanti, U'ut; Suprayitno, Eko (Journal of Islamic Economic Laws, 2025)
The financing distribution by Islamic banks plays a crucial role in driving national economic growth. In its practice, financing is not without risks. Therefore, Islamic banks must manage risk and analyze the factors influencing their financing distribution. The research aims to analyze the influence of the Minimum Statutory Reserve (GWM), Third-Party Funds (DPK), Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Non-Performing Financing (NPF) on the financing distribution of Islamic commercial banks.The research employed a quantitative research method using an explanatory approach. The researcher obtained the secondary data from the bank websites and used the purposive sampling technique. The research population and sample comprised Islamic commercial banks in Indonesia from 2018 to 2023. The analysis was conducted using panel data regression and the E-Views 12 software. The research results indicate that, partially, the DPK and FDR positively and significantly influence the Financing Distribution. In contrast, the CAR significantly and negatively influences Financing Distribution. In addition, the GWM and NPF do not show a significant influence on the Financing Distribution. Simultaneously, the GWM, DPK, CAR, FDR, and NPF significantly influence the Financing Distribution.